Case Report: A 47-Year-Old Man with Coagulopathy Due to a Snakebite - Purba, Reynardo Kurnia Hadiyanto; Sio, Beatrix; Tanto, Ayu Cyntia; Prijopranoto, Heri Sutrisno; Marpaung, Amrul (Green Publisher Indonesia, 2025)
Venomous snakebite is a medical emergency commonly occurring in tropical regions and can lead to severe systemic complications, including Venom-Induced Consumption Coagulopathy (VICC). This condition is characterized by activation of the coagulation pathway by snake venom enzymes, leading to massive consumption of clotting factors. A 47-year-old male presented with severe pain, progressive swelling, and subcutaneous bleeding of the left lower limb following a suspected snakebite while working in a forest. Laboratory examination revealed an unmeasurably prolonged prothrombin time (>150 seconds), indicating severe coagulopathy. The suspected envenomation was caused by Trimeresurus insularis, a venomous pit viper endemic to East Nusa Tenggara, Indonesia. Due to the unavailability of antivenom, the patient was managed supportively with Fresh Frozen Plasma (FFP) transfusion and vitamin K before self-discharging against medical advice. This case highlights the critical importance of early recognition and timely antivenom administration in managing venomous snakebites. Without antivenom, the risk of life-threatening complications such as hemorrhage, organ failure, and death increases significantly. Equitable distribution of antivenom and enhanced education for healthcare providers and the community are essential to reducing snakebite-related morbidity and mortality in Indonesia.